Effectiveness of teaching motivational interview technique to third professional year medical students to improve counseling skills – An interventional study - Govindaraju S. L. Manojna; B. Devi Madhavi (MRIMS Journal of Health Sciences)
Background: Effective patient–provider communication was recognized as essential to providing high-quality medical care. In medical practice, motivational interviewing (MI) is a vital communication method. By assisting patients in exploring and resolving ambivalence and resistance to change, this directive the patient-centered counseling approach seeks to elicit behavior change. Health behavior change counseling skills were taught as a learning objective in medical curricula worldwide. However, in many medical colleges, this area of health-care education was frequently unstructured and informal. Objective: This study aimed to find out if teaching medical students how to conduct motivational interviews helped them feel more confident about their ability to advise patients on changing their health-related behaviors, such as their breastfeeding habits in the present study. Methodology: All 200 third-year medical students of a medical college participated in MI sessions for health behavior change. Antenatal and postnatal mothers completed a pre- and posttest questionnaire before and after being educated by trained medical students; later, the students completed a perception questionnaire regarding their confidence. Data were analyzed using SPSS version 17, and student perceptions were presented as percentages. Results: The mean score (knowledge) of posttests (12.53) is higher than the mean score of pretests (9.23) which is statistically significant (P = 0.000). There was a role of health education for behavioral change in improving mothers’ knowledge regarding breastfeeding, (antenatal and postnatal). Conclusion: The results of the present study demonstrated that teaching MI methods to third-year medical students could increase student confidence in giving patients advice about changing their health-related behaviors.